Black limit. Part 12: The transformation expanded with lorentsevoye - Яловенко, Сергей Николаевич (Eastern-European Journal of Enterprise Technologies, 2013)
New limitation is imposed – none body can have a mass more than a mass of black hole, in addition to light speed limitation. Based on this limitation, new formulae for the theory of relativity and extension of classical equations for mass, length, time can be obtained. Relativity of charge is shown. Formulas for charge and gravitation are extended. This paper considers the continuation of the theory of relativity based on development of the ether theory, where krypton (strong wave) is the discrete element of super fluid ether, elementary particles are represented by flat whirlpools, gravitation is given as varying density of krypton (strong wave) created by flat whirlpools. The charge is presented as a sinusoid tail stretched by a whirlpool, not coiled and created by a dipole displacement of krypton (ether). Energy of particles is presented as transformation of progressive wave energy into rotational whirlpool energy. It is shown that the gravitation of black hole is flat, not circular. The coefficient of star light refraction is presented.